Human and Zoonotic Dermatophytoses: Epidemiological Aspects - Segal, Esther; Elad, Daniel (Frontiers in Microbiology, 2021)
Introduction: Dermatophytes are a group of molds characterized by the ability to produce keratinases, thereby carving out for themselves specific ecological niches. Their traditional division into three genera, Trichophyton, Microsporum and Epidermophyton have been expanded to nine and the species in each genus were modified. Dermatophytes are among the most prevalent causes of human and animal mycoses. Their epidemiology is influenced by various factors. These factors may be evolutive such as the predilected environment of the fungus, namely humans (anthropophilic), animals (zoophilic) or environment (geophilic), are evolutionary and thus may require centuries to develop. Many other factors, however, result from a variety of causes, affecting the epidemiology of dermatophytoses within a shorter time frame. Objective: This review aims at summarizing the factors that have modified the epidemiology of dermatophytoses during the last decades. Results: Geographic and climatic conditions, demography such as age and gender, migration, socio-economic conditions, lifestyle, and the environment have had an impact on changes in the epidemiology of dermatophytoses, as have changes in the pattern of human interaction with animals, including pets, farm and wild animals. A typical example of such changes is the increased prevalence of Trichophyton tonsurans, which spread from Latin America to the United States and subsequently becoming a frequent etiological agent of tinea capitis in Africa, Middle East and other areas. Conclusions: The comprehension of the epidemiology of dermatophytoses has a major bearing on their prevention and treatment. Since it is undergoing continuous changes, periodic assessments of the most recent developments of this topic are required. This article aims at providing such an overview.